The evaluation model of the impact of corporate social responsibility on firm performance: A empirical study in the maritime transportation of Vietnam - Long Van Hoang; Hien Thi Dieu Vo (Cogent Business & Management, 2023)
This paper aims to investigate empirically the impact of corporate social responsibility (CSR) on firm performance (FP) with the maritime transportation industry of Vietnam as a case study. To evaluate the research model, this study surveyed 145 shipping companies (SCs) across Vietnam, and adopted a structural equation modeling (SEM) to test the proposed hypotheses. It is found: (1) CSR measures significantly directly affect FP and indirectly influence through customer loyalty (CL), (2) CSR initiatives improve customer satisfaction (SAT), and CL. Based on empirical results, this research suggests some management recommendations for SCs to improve their CSR initiatives and, in turn, boost their performance.
Keywords: 650; corporate social responsibility; customer loyalty; firm performance; maritime transportation; SEM